DAMPAK MEDIA SOSIAL TERHADAP PEMBENTUKAN IDENTITAS SOSIAL ANAK DI ERA DIGITAL: SEBUAH TINJAUAN SOSIOLOGIS DI KOTA MAKASSAR - Andi Nurlela; Atma Ras; Musrayani Usman (Universitas Halu Oleo (UHO), 2024)
This study aims to analyze the impact of social media on the formation of children's social identity in the city of Makassar in the digital age. Using a qualitative approach and case study method, this research involves children aged 10-15 years who are actively using social media platforms such as Instagram, TikTok, and Facebook. The results show that social media plays a crucial role in the process of social identity formation through symbolic interaction, where children construct an ideal self-image to gain recognition and validation from their peers. However, alongside these benefits, children also face social pressures to always appear